2018
DOI: 10.1108/lodj-08-2017-0240
|View full text |Cite
|
Sign up to set email alerts
|

Charismatic and corrective leadership dimensions as antecedents of employee safety behaviours

Abstract: Purpose The purpose of this paper is to investigate idealised influence under transformational leadership and active management-by-exception (MBE-A) under transactional leadership as the predictors of employee safety behaviours among engineers and technicians in the Ghanaian power transmission subsector. Design/methodology/approach The study employed a cross-sectional survey design and a quantitative approach to gather data from 278 respondents through the use of a structured questionnaire. Covariance-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 47 publications
2
25
1
Order By: Relevance
“…The first finding of the study showed that transformational leadership had a positive influence on safety behaviours of the engineers and technicians. This finding is in line with several other empirical studies (Dartey-Baah and Addo, 2018; Fernández-Muñiz et al , 2014; Hoffmeister et al , 2014; Kapp, 2012; Lu and Yang, 2010; Mullen et al , 2017; Smith et al , 2016) that found that transformational leadership style and its aspects and dimensions predicted and related positively to safety behaviours. However, these findings go partially contrary to those of Clarke (2013) and Jiang and Probst (2016) who only found a positive influence of transformational leadership on safety participation but not on safety compliance.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The first finding of the study showed that transformational leadership had a positive influence on safety behaviours of the engineers and technicians. This finding is in line with several other empirical studies (Dartey-Baah and Addo, 2018; Fernández-Muñiz et al , 2014; Hoffmeister et al , 2014; Kapp, 2012; Lu and Yang, 2010; Mullen et al , 2017; Smith et al , 2016) that found that transformational leadership style and its aspects and dimensions predicted and related positively to safety behaviours. However, these findings go partially contrary to those of Clarke (2013) and Jiang and Probst (2016) who only found a positive influence of transformational leadership on safety participation but not on safety compliance.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the current finding is in partial agreement with that of Jiang and Probst (2016) who found no significant correlation between passive leadership and safety participation. However, this finding goes contrary to those of Clarke (2013), Hoffmeister et al (2014), Kapp (2012), Lu and Yang (2010) who found that transactional leadership and its dimension of contingent reward had a significant relationship and influence on safety behaviours; and partially contrary to that of Dartey-Baah and Addo (2018) which indicated that active management-by-exception predicted safety participation but not safety compliance. This finding is however not too surprising with regard to the context of the study.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Among the dimensions of the transactional leadership style as articulated and measured by Bass and Avolio (2004), only management-by-exception-active had a positive relationship with SCBs. This finding is consistent with the views of Dartey-Baah and Addo (2018) that active management-by-exception when properly practiced can foster safety participation among employees. Neal and Griffin (2006) explained that safety behaviors that reinforce safety participation should represent SCBs because they are more discretionary.…”
Section: Discussionsupporting
confidence: 90%
“…These concepts assess the relationship and exchanges that exist between leaders and followers in a bid to bring organisations goals into fruition (Dartey-Baah, 2015). The transformational and transactional leadership styles do not consider leadership as a one-directional form of influence but rather as an interaction and emphasise the important role played by followers in the leadership process (Dartey-Baah and Addo, 2018). This study focussed on transformational and transactional leadership styles.…”
Section: Introductionmentioning
confidence: 99%